Gamifying Sociological Surveys Through Serious Games—A Data Analysis Approach Applied to Multiple-Choice Question Responses Datasets - Alexandros Gazis; Eleftheria Katsiri (Computers)
E-polis is a serious digital game designed to gamify sociological surveys studying young people’s political opinions. In this platform game, players navigate a digital world, encountering quests posing sociological questions. Players’ answers shape the city-game world, altering building structures based on their choices. E-polis is a serious game, not a government simulation, aiming to understand players’ behaviors and opinions; thus, we do not train the players but rather understand them and help them visualize their choices in shaping a city’s future. Also, it is noticed that no correct or incorrect answers apply. Moreover, our game utilizes a novel middleware architecture for development, diverging from typical asset-prefab-scene and script segregation. This article presents the data layer of our game’s middleware, specifically focusing on data analysis based on respondents’ gameplay answers. E-polis represents an innovative approach to gamifying sociological research, providing a unique platform for gathering and analyzing data on political opinions among youth and contributing to the broader field of serious games.